IS ACCOUNTANCY A SCIENCE? - Kelley, Arthur C. (The Accounting Review, 1941)
Abstract Since accounting is the method and means of recording, measuring and interpreting business and economic events, it is evident that accounting like statistics, is a technique and tool of social science, applicable particularly to business enterprises and other accounting entities. The accounting procedure must be used in a scientific manner in order to obtain results, which present true and impartial pictures of economic and business facts. In other words, if accounting is really to fill the role assigned to it as a means of economic control, it must grow out of its traditional, rule of thumb procedures and assume the stature of an objective, impersonal social science. There is considerable evidence today of a growing recognition among accountants that such a development is not only possible but also very necessary and that the time has now come when the practice of accounting ought to be placed on a genuinely objective basis, so that the special desires and interests of individual accountants and business managers will not unduly influence findings of accountants.